2014
DOI: 10.1002/alr.21264
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal‐augmented manuka honey as a topical anti–Staphylococcus aureus biofilm agent: safety and efficacy in an in vivo model

Abstract: Sinus irrigation with MH/MGO at MGO concentrations between 0.9 and 1.8 mg/mL is both safe to mucosa and efficacious against S. aureus biofilm. MH/MGO irrigation could represent a viable treatment option for recalcitrant CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 34 publications
3
59
0
1
Order By: Relevance
“…No epithelial damage of the nasal respiratory mucosa was seen on light microscopy or transmission electron microscopy. Paramasivan et al 797 performed both a safety and efficacy study in an in vivo sheep model by performing frontal trephinations and irrigating the frontal sinuses with Manuka honey. In the safety arm, they found that a concentration of MGO up to 1.8 mg/mL did not cause any epithelial injury on standard microscopy and scanning electron microscopy; however, at an MGO concentration of 3.6 mg/mL, patchy ciliary denudation of the epithelium was demonstrated.…”
Section: S93mentioning
confidence: 99%
“…No epithelial damage of the nasal respiratory mucosa was seen on light microscopy or transmission electron microscopy. Paramasivan et al 797 performed both a safety and efficacy study in an in vivo sheep model by performing frontal trephinations and irrigating the frontal sinuses with Manuka honey. In the safety arm, they found that a concentration of MGO up to 1.8 mg/mL did not cause any epithelial injury on standard microscopy and scanning electron microscopy; however, at an MGO concentration of 3.6 mg/mL, patchy ciliary denudation of the epithelium was demonstrated.…”
Section: S93mentioning
confidence: 99%
“…Topical delivery of antimicrobials to the nose and paranasal sinuses in nebulizers and irrigations has been reported to be beneficial against biofilm-associated chronic rhinosinusitis (9,10). Another promising approach is the use of gels that can be directly instilled into the sinuses.…”
mentioning
confidence: 99%
“…Honey through different studies has almost equal or slightly superior effects when compared with conventional treatments for acute wounds [34] especially pan-or multidrug-resistant bacterial infections [5]. Consequently; honey is getting worldwide attention as a topical therapeutic agent for wound infection and potential future candidate for systemic infections [42].…”
Section: Discussionmentioning
confidence: 99%